Indu ne patro : duniyānī utpatti ane prārambhanā divasonuṃ baḷakone māṭe lakheluṃ tūṅka varṇana - Nehru, Jawaharlal, 1889-1964 (SAMP early 20th-century Indian books project, 1944)
Collection of letters from Jawaharlal Nehru to his young daughter, Indira Gandhi, dealing with the begining of the Earth, man's awareness of Himself, and the history and civilization of the ancient world.